PEMBERIAN PUPUK ORGANIK BIO-SLURRY CAIR DAN MACAM MULSA ORGANIK PADA BUDIDAYA TERONG (Solanum melongena L.) VARIETAS JENO FI: types of organic mulch, eggplant - hadi, pramono hadi; Al Rizal, Miftah Firdaus; Rahayu, Tri (Universitas Boyolali, 2022)
ABSTRACT This study aims to determine the effect of application of liquid bio-slurry organic fertilizer and kinds of organic mulch on the cultivation of eggplant (Solanum melongena L.) Jeno F1 varieties.. This research was conducted from November to February 2020 in Kuncen Waru Village, Baki District, Sukoharjo Regency. This study used an environmental design with a basic pattern Randomized Complete Block Design (RCBD) consisting of 2 treatment factors with 9 treatment combinations and repeated 3 times. The first treatment factor, giving mulch (M) consisting of 3 levels M1 = straw mulch M2 = reed mulch and M3 = bamboo leaf mulch, the second treatment factor, giving concentration of bio-slurry liquid (S) consisting of 3 levels S1 = 5 ml bio-slurry/ liter water, S2 = 10 m bio-slurry / liter water and S3 = 15 ml bio-slurry / liter water. The results of this study indicate that the treatment of organic mulch has a very significant effect on the weight of fruit per plant, the number of fruits per plant and the fresh weight per plant, and also has a significant effect on the dry weight per plant. Liquid bio-slurry fertilizer has a very significant effect on fruit weight per plant, number of fruits per plant and fresh weight per plant, and also has a significant effect on dry weight per plant. The best combination is M1S3 straw organic mulch treatment and bio-slurry 15 ml / liter of water. This gives the highest yield in the parameters of plant height 59.89 cm, fruit weight per plant 146.54 g, number of fruits per plant 6.56, fruit diameter 5.06 cm, fresh biomass weight per plant 62.20 g, and weight dry biomass per plant 39.06 g. Keywords: types of organic mulch, bio-slurry liquid, eggplant